Molecular mapping of stomatal‐conductance‐related traits in durum wheat (Triticum turgidum ssp. durum). (1st February 2013) - Panio, G.; Motzo, R.; Mastrangelo, A.M.; Marone, D.; Cattivelli, L.; Giunta, F.; De Vita, P.
Abstract The most promising traits identified in wheat to raise yield potential via an increase in biomass accumulation are stomatal conductance and stomatal‐conductance‐related traits, such as carbon isotope discrimination (CID) and photosynthetic rate. The evaluation of the extent of genetic variation and the mapping of chromosomal regions controlling these traits are essential for the development of effective breeding strategies in durum wheat. A population of 161 F2‐derived, F8–F9 recombinant inbred lines obtained from a cross between durum wheat (Triticum turgidum ssp. durum) cultivars Ofanto and Cappelli was phenotyped for heading date, plant height, leaf porosity, CID and chlorophyll concentration (estimated through the SPAD index) for 2007/2008 and 2008/2009 seasons, at Ottava, Sardinia (Italy) under irrigated conditions. The genotype mean heritability for leaf porosity, CID and chlorophyll concentration was moderate in size. Six quantitative trait loci were detected for leaf porosity, four for chlorophyll concentration, but only one for CID, because of the small variation expressed in the population for this trait under these experimental conditions. The quantitative trait loci for leaf porosity located on chromosome 3B appear to be more stable with respect to the others, and different microsatellite markers are positioned within the interval of the quantitative trait loci, or in their vicinity, that represent useful tools in programmes for selection assisted by molecular markers.